2023
DOI: 10.29244/jpsl.13.1.76-87
|View full text |Cite
|
Sign up to set email alerts
|

THE UTILIZATION OF DURIAN PEELS (Durio zibethinus) FOR THE MANUFACTURING OF CHARCOAL BRIQUETTES AS ALTERNATIVE FUEL

Abstract: Durian peels is a biomass waste that can be used as an alternative fuel in charcoal briquettes. Durian peels contains combustible materials, namely high cellulose (50%-60%) and lignin (5%) and low starch (5%). This study aims to determine the characteristics of charcoal briquettes from durian skin waste using adhesive from sago starch as an alternative fuel. The adhesive used is adhesive from sago flour, which is 3% of the weight of the charcoal used. In this study, 500 g of charcoal was used, so that the adhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…Wirabuana & Alwi reported that durian skin charcoal briquettes with starch adhesive had a water content of 5.85% [18]. Sitti Rahmawati et al also said in their research that briquettes made from carbonated durian skin waste with sago starch adhesive had a low water content of 3.6% [10]. However, the results of the water content of biobriquettes in this study are in line with the results reported by Merry M. Mitan et al, who stated that durian skin biobriquettes with starch adhesive had a water content of > 10% [9].…”
Section: Moisture Contentmentioning
confidence: 96%
See 1 more Smart Citation
“…Wirabuana & Alwi reported that durian skin charcoal briquettes with starch adhesive had a water content of 5.85% [18]. Sitti Rahmawati et al also said in their research that briquettes made from carbonated durian skin waste with sago starch adhesive had a low water content of 3.6% [10]. However, the results of the water content of biobriquettes in this study are in line with the results reported by Merry M. Mitan et al, who stated that durian skin biobriquettes with starch adhesive had a water content of > 10% [9].…”
Section: Moisture Contentmentioning
confidence: 96%
“…The processing of durian peel into biobriquette is possible, giving durian peel more added value as a product. Several research has been accomplished in terms of briquetting durian peel [8]- [10].…”
Section: Research Backgroundmentioning
confidence: 99%
“…Durian peel had a volatile matter of 22%, and sewage sludge contained a volatile matter of 27.5%. The previous study reported that the briquette from durian peel has a comparable volatile matter of 21.13% [21]. Carbonization lowers the volatile matter value in biomass because the volatile particle is vapored at the temperature of 500°C [22].…”
Section: Proximate Analysis Of Carbonized-durian Peel and Sewage Sludgementioning
confidence: 97%
“…Silika adalah salah satu komponen abu yang paling umum dan berdampak negatif terhadap kualitas briket [26]. Menurut Hendra dan Winarni (2003), silika mempunyai kemampuan menurunkan nilai kalor batubara [27], dan menurut Nurhilal dan Suryaningsih (2018), kandungan abu yang tinggi pada briket dapat menurunkan nilai kalor sehingga mengakibatkan terbentuknya kerak pada saat dibakar [20], sehingga menurunkan kualitas briket yang dihasilkan [28], hal ini terlihat pada senyawa pada Gambar 3, Gambar 4, Gambar 5, dan Gambar 6. Jika kandungan salah satu campuran briket biomassa tinggi maka kadar airnya akan rendah.…”
Section: Kadar Abuunclassified